United States-China multilateralism in the age of military AI - Daniel Araya; Alex He (Centre for International Governance Innovation (CIGI), 2024)
This paper examines the shifting global power dynamics driven by the rise of China and the rapid advancements in artificial intelligence (AI). Taken together, a rising tide of high-tech weapons development and a return to great power rivalry are setting the conditions for a tectonic shift in the global security landscape. The paper highlights the strategic challenges posed by these trends and underscores the critical need for multilateral cooperation in managing a new multipolar world order. It calls for strengthened diplomatic and military frameworks to mitigate risks, drawing on historical precedents in arms control to guide future governance of AI in military applications.
Keywords: 330